2021
DOI: 10.1002/er.6408
|View full text |Cite
|
Sign up to set email alerts
|

Pressure‐dependent elasto‐mechanical stability and thermoelectric properties of MYbF 3 (M = Rb, Cs) materials for renewable energy

Abstract: Pressure-dependent elasto-mechanical, thermoelectric and thermodynamic properties of two direct band gap halide perovskites MYbF 3 (M = Rb, Cs) have been investigated using density functional theory calculations. These

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…Moreover, the density functional theory method has been proven to be one of the most efficient and accurate methods in the calculations of perovskite structures. 19–23…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the density functional theory method has been proven to be one of the most efficient and accurate methods in the calculations of perovskite structures. 19–23…”
Section: Introductionmentioning
confidence: 99%
“…A vacuum of 30 Å was provided along c-direction to avoid the effect of interlayer interaction. It has been shown that the DFT method is considered to be one of the most accurate methods for calculating the electronic structure of solids [ 54 , 55 , 56 ].…”
Section: Methodsmentioning
confidence: 99%
“…The density functional theory (DFT) method has proven to be one of the most accurate methods for the computation of the electronic structure of solids. [44][45][46][47][48][49][50] All the calculations were implemented using the Vienna Ab initio Simulation Package (VASP 5.4.4) based on DFT adopting the projector augmentedwave method (PAW). 51,52 The generalized gradient approximation (GGA) of Perdew-Burke-Ernzerhof (PBE) has been selected to approximate the exchange-correlation energy.…”
Section: Calculation Of Electronic Densitiesmentioning
confidence: 99%